Naum Grebnev – translator of Armenian poetry - JANPOLADYAN, MAGDA (Bulletin of Yerevan University H: Russian Philology, 2021)
The article features Naum Grebnev`s translations of Armenian poetry. Grebnev`s translation principles are presented, translations of Kuchak hairens (couplets with a single coherent theme), a number of works from Hovhannes Tumanyan, in particuar the quatrains, as well as the chapters from Narekatsi “Book of Lamentation” are analyzed in detail. The translations by Grebnev of other poets of Armenian Middle Ages are also mentioned. It is noted, that, through his highly artistic translations, Grebnev revealed numerous pages of Armenian poetry to the Russian readers.